A tale of two worlds: a (very) select overview of socio-legal studies in Belgium. Issue 1 (23rd February 2016) - Parmentier, Stephan
Abstract: Socio-legal studies in Belgium represent a diverse patchwork of many topics studied from many angles. This paper first presents a brief historical account of socio-legal studies and their organisation, in the north and south of the country. It has no ambition to give a full overview of socio-legal studies in Belgium, let alone be exhaustive. It merely focuses on the content and features of two topics that have constituted major strands of research over the last thirty years: courts and dispute processing, and public opinion about law and justice. It ends with some reflections on the nature of Belgian socio-legal research, as well as some recommendations on future orientations.